Leadership and Teacher Well-Being: Investigating the Relationship Between Educational Leadership and Teacher Well-Being, and How Leaders Can Create Supportive and Healthy Work Environments - ABDELRAZEQ, ADEL (2024)
In this detailed study, the dissertation delves into the significant relationship between educational leadership and teacher well-being within private schools in Sharjah and Ajman, UAE. The research addresses a critical problem statement: understanding how leadership practices in educational settings influence the well-being and job satisfaction of teachers. The aim is to uncover specific leadership behaviours that contribute to or detract from teacher well-being. The study's main research question probes the connection between various leadership styles and their effects on teachers' professional satisfaction and stress levels. To provide a comprehensive analysis, the dissertation draws upon key theories and previous studies that link educational leadership with teacher well-being, although these specific theories and studies are not detailed in the abstract. Employing a mixed-methods approach, the research combines qualitative data from interviews with school leaders and quantitative data from teacher surveys, offering a holistic view of the leadership impact on teacher well-being. The key findings highlight the importance of supportive, communicative, and empowering leadership practices in fostering positive work environments for teachers. While the study offers significant insights, it acknowledges its limitations, including its geographical focus on Sharjah and Ajman, suggesting that future research could broaden the scope to include various educational contexts and cultures. In conclusion, the dissertation asserts a strong claim: effective leadership is paramount in creating an environment that nurtures teacher well-being, which is crucial for maintaining high educational standards and ensuring positive student outcomes. The inferences drawn underscore the necessity for educational leaders to adopt practices that prioritise teacher welfare, highlighting its ripple effect on the broader educational ecosystem. Keywords: educational leadership, teacher well-being, private schools, UAE, leadership practices, job satisfaction, stress levels, mixed-methods approach, supportive leadership, empowerment in education